Milk yield and composition of crossbred cows in the hilly Wayanad district of Kerala, India - G, RADHIKA; S, AJITHKUMAR; A, RANI; T, SATHIAN C; K, ANILKUMAR; P, USHA A; N, DINESH C (The Indian Journal of Animal Sciences, 2012)
Lactation milk yield and milk constituents like milk fat and solids-not-fat (SNF) decide the economics of dairy cattle rearing. Data from hilly districts like Wayanad are seriously lacking and hence the present study was undertaken, where 268 cows from 5 centres of Wayanad were selected for recording lactation milk yield. 929 milk samples from these cows were analyzed for fat, solids not fat (SNF) and total solids in different stages of lactation. The overall least squares mean for lactation milk yield, peak yield, milk fat and SNF percentages were 2118.796±139.578 kg, 10.627±0.6120 kg, 3.515±0.080 and 8.359±0.042 respectively. The least squares analysis of variance revealed that centre had significant effect on peak yield, lactation milk yield, milk fat, SNF and total solids percentages, whereas parity and season of calving had no significant effect.